Working Capital Management Relationship to Profitability of Plastic and Packaging Sub-Sector Companies on the Indonesia Stock Exchange: Working Capital Management Relationship to Profitability of Plastic and Packaging Sub-Sector Companies on the Indonesia Stock Exchange - rachyu purbowati (Journal of Accounting Research, Utility Finance and Digital Assets, 2022)
The purpose of this study isto determine the influence of working capital management consisting of variables Cash Turnover, Inventory Turnover, Working Capital Turnover affecting profitability in Plastic and Packaging Sub-Sector companies listed on the IDX. The research approach uses quantitative descriptive methods. The population that will be used is the financial report data of plastic and packaging sub-sector companies listed on the Indonesia Stock Exchange with the purposive sampling sampling method with the criteria of plastic and packaging sub-sector companies listed on the Indonesia Stock Exchange which have complete financial statements in the period 2011 - 2020 so that the data used are 60 financial statement data. Data analysis uses multiple linear regression. The results showed that thereis a significant positive influence of cash turnover on profitability, meaning that the higher the cash turnover, the higher the profitability, thehigher the cash turnover will be better because this means that the higher the efficiency of cash use and the greater the profit obtained. There is a significant positive effect of inventory turnover on profitability, meaning that the higher the inventory turnover, the higher the profitability, the higher the inventory turnover, the higher the profit obtained. There is no effect of capital turnover on profitability, which means that the rise and fall of capital turnover does not affect the rise and fall of profitability.